The Implementation of National Health Insurance (JKN) in Kediri City - Mahardika, Mahardika (Jurnal Ilmiah Administrasi Publik, 2016)
This article aims to implementation of National Health Insurance in Kediri City that was not going smoothly and to know about advantages and disadvantages of the implementation of national health insurance (JKN) in Kediri City. The implementation of JKN was not going well, because participant did not know their first health service and they did not know about procedure of JKN. So every stakeholder like BPJS (Social Security Administrative Bodies), Health Departement, and Health facility must give information to participant about the regulation. The advantages are: the new rules are immediate to implement, Puskesmas has adequate facility, P-care program, Identity card can use to get treatment in Puskesmas. The disadvantages are priority, lack of information, system information, lack information between health facility, and the 40% of capitation fund.